2006
DOI: 10.1111/j.1470-6431.2006.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Escaping a silent world: profound hearing loss, cochlear implants and household interaction

Abstract: For some people with profound hearing loss, cochlear implants offer a way back to patterns of communication that most of us take for granted. Travel, shopping and work contexts are largely dependent on the ability to recognize and respond to speech. This study examined implant user and partner perspectives on problems and coping strategies. The aim was to map the experiences of adults and their hearing partners living with deafness; and the changes brought about by cochlear implant use. Information was gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This is consistent with other research findings suggesting that hearing difficulties contribute to interpersonal and emotional problems (Hétu et al 1993;Lormore & Stephens 1994;Stephens et al 1995;Brooks et al 2001;Anderson & Noble 2005). Another study of adult cochlear implant users and their spouses found that hearing difficulties limited the couples' social life and had an effect on their marital relationship (Ross & Lyon 2006), with spouses in this study also taking on additional responsibilities for their partners, including that of being carer or interpreter. They found higher relationship satisfaction in couples that made fewer negative attributions to the character of the person with the hearing impairment.…”
Section: Factors Associated With Third-party Disability In Spouses Ofmentioning
confidence: 68%
See 1 more Smart Citation
“…This is consistent with other research findings suggesting that hearing difficulties contribute to interpersonal and emotional problems (Hétu et al 1993;Lormore & Stephens 1994;Stephens et al 1995;Brooks et al 2001;Anderson & Noble 2005). Another study of adult cochlear implant users and their spouses found that hearing difficulties limited the couples' social life and had an effect on their marital relationship (Ross & Lyon 2006), with spouses in this study also taking on additional responsibilities for their partners, including that of being carer or interpreter. They found higher relationship satisfaction in couples that made fewer negative attributions to the character of the person with the hearing impairment.…”
Section: Factors Associated With Third-party Disability In Spouses Ofmentioning
confidence: 68%
“…Research has shown that as a result of hearing difficulties, family members, and in particular, spouses often take on additional responsibilities, and family roles are altered (Hétu et al 1988;Hallberg & Barrenäs 1993;Morgan-Jones 2001;Ross & Nerina Scarinci, Linda Worrall, and Louise Hickson Communication Disability Centre, School of Health and Rehabilitation Sciences, The University of Queensland, Australia. Lyon 2006; Yorgason et al 2007;Scarinci et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…CPs can also experience increased stress when serving as the "ears" of the person who is HOH (Hétu et al, 1988). Moreover, within a marriage, profound hearing loss can lead to the normal-hearing partner adopting additional responsibilities and becoming an interpreter and caregiver (Ross, 2007). Denial of hearing impairment by the person who is HOH can result in conflict and even crisis within a couple, highlighting the importance of acknowledging the disability (Armero, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for lower satisfaction scores in accessing support from local agencies include limited availability of preferred options, educational supports, and service providers with specialized training. The importance of a variety of informational supports has been underscored in several recent studies (Most & Zaidman-Zait, 2003;Ross & Lyon, 2007;Zaidman-Zait, 2007). In Most and Zaidman-Zait (2003), 22.7% of the parents surveyed reported that they lacked information on communication, and 36.4% reported that they lacked technical information.…”
Section: Impact and Satisfaction With Family Lifementioning
confidence: 99%
“…This finding coincides with Nikolopoulos, Lloyd, Mphil, and O'Donoghue (2001), in which 98% of parents indicated that their child's outcomes after cochlear implantation met or surpassed their expectations. There is a large body of literature documenting improvements in speech perception, speech production, and general language skills following cochlear implantation (Bohnert, Spitzlei, Lippert, & Keilmann, 2007;Kirk, Miyamoto, Ying, Perdew, & Zuganellis, 2003;Ross & Lyon, 2007;Sharma, Dorman, Spah, & Todd, 2002;Zwolan et al, 2004).…”
Section: Satisfaction With Child Outcomes In Communication Skillsmentioning
confidence: 99%